2020
DOI: 10.3844/ajavsp.2020.67.72
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Rumen Fermentability of the Pelleted Feed Containing Water Spinach (Ipomoea aquatica

Abstract: An in vitro technique based on two stages of batch culture was used to clarify fermentability and digestibility of pellet feed containing water spinach (Ipomoea aquatica). The portion of Pennisetum purpureum in the pellet feed was substituted with Ipomoea aquatica at respective levels of 0% (T1), 20% (T2), 40% (T3) and 60% (T4). The treatments were allocated in a completely randomized design with 5 replicates of each. The results showed that the substitution of water spinach in pellet did not effect on pH, amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The water spinach waste was dried and can be used as potential feed for small ruminants during the dry season to reduce high feeding costs, as Gao et al [1] stated that high feeding costs are one of the farming problems. Water spinach waste contains 10.65% of crude protein (CP), which is better than Pennisetum purpureum (CP: 6.70%) as a fiber source [2] . Maulana et al [3] showed that local sheep fed water spinach ad libitum had average daily gain (ADG) values of about 118.19 gm (thin-tailed sheep) and 130.39 gm (“Garut” sheep).…”
Section: Introductionmentioning
confidence: 99%
“…The water spinach waste was dried and can be used as potential feed for small ruminants during the dry season to reduce high feeding costs, as Gao et al [1] stated that high feeding costs are one of the farming problems. Water spinach waste contains 10.65% of crude protein (CP), which is better than Pennisetum purpureum (CP: 6.70%) as a fiber source [2] . Maulana et al [3] showed that local sheep fed water spinach ad libitum had average daily gain (ADG) values of about 118.19 gm (thin-tailed sheep) and 130.39 gm (“Garut” sheep).…”
Section: Introductionmentioning
confidence: 99%